2022
DOI: 10.1088/1755-1315/1098/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Waste Community: Sustainable Living in Digital Era

Abstract: Waste is a problem in our society and still depends on the conventional management system. This paper discusses the interrelationship among virtual social media, waste management practice, and community-based economics in supporting sustainability and zero waste in the digital era. In particular, it attempts to identify the potential connections of social media in extending new environmental practices. Observation of two types of Indonesian Instagram accounts (personal and group) of waste-related illustrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…In another publication, the role of social networks was validated, obtaining that it is based on experience, position, and level of activity (Fayez et al, 2023) and that, in the virtual world, platforms play an important role in different aspects such as the personal sphere (Redyantanu et al, 2022).…”
Section: Contents In Virtual Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another publication, the role of social networks was validated, obtaining that it is based on experience, position, and level of activity (Fayez et al, 2023) and that, in the virtual world, platforms play an important role in different aspects such as the personal sphere (Redyantanu et al, 2022).…”
Section: Contents In Virtual Communitiesmentioning
confidence: 99%
“…The term virtual communities is relatively new since these spaces had a boom after the pandemic, and these publications are part of the studies that investigated this virtual phenomenon. For example, in Spain, the virtualization of the reality of these communities was proposed through the search for messages, meanings, and frameworks (Goyez 2021), Another study sought to examine how young people in a high school build a socialization link (Fernández and Gutierrez, 2017), while another one described the interactions of an online community and the content shared among users (Cervi, 2019); Amo & Garcia (2022) described the attitudes, knowledge, and competencies of the fanon of a community; in Indonesia, the interrelationship between networks and waste was analyzed (Redyantanu et al, 2022); in Saudi Arabia, the role of social networks in a virtual environment was validated (Fayez, et al, 2023); in Mexico, the digital skills of group members were identified, describing the actions and resources they share in a community (Cordero and Gonzales, 2022).…”
Section: Introductionmentioning
confidence: 99%